Comparison of laparoscopic and open radical hysterectomy in cervical cancer patients with tumor size ≤2 cm. Issue 5 (9th April 2020) - Chen, Xu; Zhao, Na; Ye, Piaopiao; Chen, Jiahua; Nan, Xingwei; Zhao, Hongqin; Zhou, Kai; Zhang, Yuyang; Xue, Jisen; Zhou, Haihong; Shang, Huiling; Zhu, Hanxiao; et al.
Abstract : Objective: There is recent evidence that demonstrates worse oncologic outcomes associated with minimally invasive radical hysterectomy when compared with open radical hysterectomy, particularly in patients with tumors >2 cm. The aim of our study was to retrospectively evaluate the oncological outcomes between laparoscopic and open radical hysterectomy in International Federation of Gynecology and Obstetrics(FIGO) 2009 stage IB1 (FIGO 2009) cervical cancer patients with tumor size ≤2 cm. Methods: A retrospective review of medical records was performed to identify patients who underwent either laparoscopic or open radical hysterectomy during January 2010 and December 2018. Inclusion criteria were: (1) histologically confirmed cervical cancer including all histological types; (2) FIGO 2009 stage IB1; (3) tumor size ≤2 cm (determined by pelvic examination, magnetic resonance imaging or transvaginal ultrasound); (4) had undergone radical hysterectomy (type II or III) with pelvic and/or para-aortic lymphadenectomy as primary surgical treatment; (5) had follow-up information. Patients with FIGO 2009 stage IA1 or IA2, tumor size >2 cm, or who received neo-adjuvant chemotherapy before surgery, those with cervical cancer incidentally found after simple hysterectomy, or with insufficient data were excluded. Concurrent comparison between the laparoscopic and open cohorts was made for disease-free survival and overall survival. Results: A total of 325 cervical cancer patients were included; of these, 129 patients underwent laparoscopic surgery and 196 patients had open surgery. The median follow-up times were 51.8 months (range 2–115) for laparoscopic surgery and 49.5 months (range 3–108) for open surgery. Patients in the laparoscopic group had significantly worse 5 year disease-free survival than those in the open group (90.4% vs 97.7%; p=0.02). There was no significant difference in 5 year overall survival between groups (96.9% vs 99.4%, p=0.33). The Cox proportional hazards regression analysis indicated that laparoscopic surgery was associated with lower disease-free survival compared with open surgery (adjusted hazard ratio 4.64, 95% CI 1.26 to 17.06; p=0.02). In patients with non-squamous cell carcinoma or with grade II–III, laparoscopic surgery had a significantly worse 5 year disease-free survival compared with the open surgery group (74% vs 100%, p=0.01,  and 88.8% vs 98.0%, p=0.02, respectively). Conclusion: Laparoscopic radical hysterectomy was associated with worse disease-free survival for stage IB1 (FIGO 2009) cervical cancer patients with tumor size ≤2 cm compared with open radical hysterectomy. Further studies may shed additional light on the impact of minimally invasive surgery in this low-risk patient population.